Abstracts Presented at the American Chemical Society National Meetings: Analysis of Their Characteristics. Issue 3 (3rd July 2019) - Salisbury, Lutishoor; Omolewu, Abayomi; Smith, Jeremy J.
ABSTRACT: This paper analyzes the abstracts from the 244th – 248th American Chemical Society national meetings, 2012–2014 for the Divisions of Biological Chemistry and Organic Chemistry. The main objective of the study was to identify the percentage of abstracts that were published as related papers and the time it took to do so. It also investigated likely factors that determined whether the abstracts will be published as papers. These factors included the number of author(s) per abstract, the number of institutions involved in the research, and the country of origin of the research. The paper also highlights the percentage of papers that were published before and after the conferences and the quality of the journals in which they were published. The citation characteristics of the articles published before and after the conference are also covered.